2024
DOI: 10.3390/s24020314
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Glass Beads in Ammonium Nitrate Solution and Compensation of Signal Losses

Erik Spoor,
Matthias Rädle,
Jens-Uwe Repke

Abstract: In the present study, the influence of disperse systems on Raman scattering was investigated. How an increasing particle concentration weakens the quantitative signal of the Raman spectrum is shown. Furthermore, the change in the position of the optimal measurement point in the fluid was considered in detail. Additional transmission measurements can be used to derive a simple and robust correction method that allows the actual concentration of the continuous phase to be determined with a standard deviation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The scope of this work was to investigate the relationship between Raman measurements and dispersive systems based on a simple system of ammonium nitrate solution and glass beads and to find a way to correct the signal losses. In the previous work [27], this was performed with only one constant particle size by taking a separate transmission measurement with a separate light source. This measurement was a reference for how much light is lost due to dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The scope of this work was to investigate the relationship between Raman measurements and dispersive systems based on a simple system of ammonium nitrate solution and glass beads and to find a way to correct the signal losses. In the previous work [27], this was performed with only one constant particle size by taking a separate transmission measurement with a separate light source. This measurement was a reference for how much light is lost due to dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…2 mm inside the cuvette. Normally, measurements would be taken in the center of a cuvette, but previous studies [27] have shown that a lower penetration depth is beneficial for the signal at higher particle concentrations. The second probe is a self-built scattering probe consisting of seven 200 µm fibers arranged in a circle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations